Physical activity in children with autism spectrum disorders - Wieczorek, Marta; Sadziak, Aleksandra (Journal of Education, Health and Sport, 2017)
PURPOSE Physical activity has been defined as each physical effort, that is muscular work, with a range of functional changes in the body that accompanies it. It is a significant factor in the proper development of humans and a component of a healthy lifestyle. Exercise is also an intrinsic element of rehabilitation for persons with various types of disabilities; one of them is autistic disorder where difficulties in social interactions, disorders in communication and occurrence of limited, stiff, stereotypical behaviour patterns are present. In this paper children with autism are the subject of interest, whereas its object is physical activity in this group. The cognitive objective is to present forms of physical activity that are available and practiced by these children. The practical objective is to expand knowledge on this subject among autistic children. MATERIALS AND METHODS The tests were carried out among parents of autistic children writing blogs concerning their children. The research method was a diagnostic poll, the tool was an independent (own) interview. Information on ten boys with autism spectrum have been presented in the paper. RESULTS Information concerning undertaken forms of physical activity among autistic boys was specified. The types of activity available and viable in autistic disorders were described. None of the boys whose details have been specified in the present work understands the rules of team sport games. All subjects, however, feel good in water environment. All subjects have sensory integration disorders, which to a large extent limits the taking up of specific forms of exercise. CONCLUSIONS Physical activity is a very important stimuli in autistic children’s development. Developmental characteristics in autistic children is connected with the type of physical activity undertaken by them.